BASOSQUAMOUS CARCINOMA OF THE HEAD - George, Gufi; Oley, Mendy H. (Riviera Publishing, 2023)
Basosquamous carcinoma (BSC) is a rare skin tumor, but it has a higher potential for invasiveness and metastasis compared to basal cell carcinoma (BCC). This case report describes a 37-year-old woman with BSC in the temporocipital region. The patient presented with the chief complaint of a lump on the back of her head for 5 years. The lump had grown, accompanied by itching and bleeding. Physical examination revealed a soft mass approximately 25 x 20 cm in size. A pre-operative diagnosis of a skin tumor was made, and elective surgical management was carried out in the Operating Room. Wide excision was performed, and the skin defect was covered with a transposition flap from the occipital base and a split-thickness skin graft. Anatomical pathology examination revealed basosquamous cell carcinoma. The patient was discharged without complaints one week after the procedure. The skin defect was closed, and hair began to grow three months after the surgery.